2023
DOI: 10.3389/fonc.2023.1101162
|View full text |Cite
|
Sign up to set email alerts
|

Hepatectomy versus transcatheter arterial chemoembolization for resectable BCLC stage A/B hepatocellular carcinoma beyond Milan criteria: A randomized clinical trial

Abstract: BackgroundHepatectomy is the recommended option for radical treatment of BCLC stage A/B hepatocellular carcinoma (HCC) that has progressed beyond the Milan criteria. This study evaluated the efficacy and safety of preoperative neoadjuvant transcatheter arterial chemoembolization (TACE) for these patients.MethodsIn this prospective, randomized, open-label clinical study, BCLC stage A/B HCC patients beyond the Milan criteria were randomly assigned (1:1) to receive either neoadjuvant TACE prior to hepatectomy (NT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Hepatectomy was conducted as previously described ( Zhong et al, 2014 ; Fang et al, 2023 ). The resection margins met R0 resection criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Hepatectomy was conducted as previously described ( Zhong et al, 2014 ; Fang et al, 2023 ). The resection margins met R0 resection criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Neither study focused exclusively on SLHCC, but included large HCCs with and without multiple nodules. The latest RCT conducted by Fang et al [19] in 2023, which also used epirubicin as their single chemotherapy agent, demonstrated improvement in 1-, 2-, and 3-year OS and DFS. Based on the outcomes of this current meta-analysis, it is evident that a combination chemotherapy regimen for N−TACE yields more favorable results than a single-agent N−TACE approach.…”
Section: Combination Agent Chemomentioning
confidence: 99%
“…On the other hand, some studies suggest that neoadjuvant TACE may improve outcomes for patients. Notably, a phase 3 randomized trial by Fang et al reported improvements in OS and progression-free survival for patients who received neoadjuvant TACE followed by hepatectomy compared to patients who did not receive preoperative TACE [ 41 ]. Patients received TACE at least twice; patients who recorded stable disease, partial response, or complete response to TACE per modified Response Evaluation Criteria in Solid Tumors (RECIST) proceeded to resection.…”
Section: Neoadjuvant/perioperative Treatmentmentioning
confidence: 99%